Image of "Globalization" in Linguistic Consciousness of Iraqi and Russian Teachers - Hassan, Hassan Issam (Al-Adab Journal, 2022)
The aim of the following research is to compare the image of globalization in linguistic consciousness among the Iraqi and Russian teachers. The research sample consisted of Iraqi and Russian teachers. The teachers were given a questionnaire consisted of 10 words and asked to write down their first reaction that comes to their minds when they see the words. After conducting the analysis, the researcher reached that the majority of reactions about globalization were positive. However, there were negative reactions for both teachers. In the light of the results of the current research, the researcher concluded a number of conclusion, including that the majority of reactions are positive- 59% for Iraqi teachers and 92% for Russian teachers- and the number of negative reactions of Iraqi teachers are more than Russian teachers- 41% for Iraqi teachers and 8% for Russian teachers- and a number of recommendations including conducting seminars on the concept of globalization and its impact on society and alerting about its benefits and risks. The researcher hopes that the analysis that he has presented here suggests more useful and accurate information and ideas about the image of globalization.